Profile of Students’ Critical Thinking Skills on the Concept of Pressure through Collaborative Sharing and Jumping Task - Rahayu, Yuyu; Supriatna, Asep; Riandi, Riandi; Hendayana, Sumar (FKIP Universitas Lampung, 2022)
This study aims to analyze the profile of critical thinking skills students in science learning with collaborative learning design sharing and jumping tasks. Indicators of critical thinking skills used are based on Ennis (1985). The method used is descriptive qualitative. Lesson design sharing & jumping tasks consist of three core activities: sharing task 1, sharing task 2, and jumping task. The instruments used are observation and audio recording of the learning process. Data were analyzed by Transcript Based Lesson Analysis (TBLA). The results of the analysis show that the collaborative learning design of sharing and jumping tasks can bring up students' critical thinking skills. The profile of students' critical thinking skills in sharing task 1 activities found 6 indicators with the highest percentage at 58%, on sharing task 2 found 12 indicators with the highest percentage at 100%, and jumping task found 9 indicators with the highest percentage at 75%. Keywords: lesson design, critical thinking skills, TBLA, sharing & jumping task. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp701-711